Proximate composition, antioxidant activities and phenolic composition of Cucumis sativus forma hardwickii (Royle) W. J. de Wilde & Duyfjes - Usmangani A Attar; Savaliram G Ghane (International Journal of Phytomedicine, 2017)
In the present investigation, nutritional, anti-nutritional and antioxidant potential of Cucumis sativus forma hardwickii was evaluated for the first time. The results revealed that leaf and fruit of Cucumis sativus f. hardwickii were rich source of ash, carbohydrate, fat, fibre and proteins. In addition, appreciable amounts of Vitamin C and E were also observed. Considerable antinutritional factors in leaf and fruit were noted which can be reduced by different processing methods. In sequential solvent extraction, methanol found to be the best in the extraction of antioxidants, which was supported with the highest antioxidant activities. Among all ¬¬the extracts, it was noted that leaves extracted with methanol had higher amount of phenols and flavonoids than fruit. In addition, the potent radical scavengers mainly phenolics were detected using RP-HPLC where tannic acid, gallic acid and hydroxybenzoic acid were also quantified in leaf and fruit. Superior antioxidant potential may be due to the presence of other bioactive compounds present in fruit. Additional research on bioactive properties of this plant is needed to explore this neglected wild cucumber for nutraceutical purpose and as a functional food.